Features of the management of the territories of National nature parks - M. Shershun; T. Mykytyn (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ, 2023)
According to the data of the State Cadastre, at the beginning of 2021, the nature reserve fund counted 8,633 territories and objects with a total area of 4.1 million hectares, which was 6.8% of the country's area. These territories are under the authority of various departments. The main purpose of protected areas is to preserve unique landscapes, species of flora and fauna for future generations. Today, the task is to increase the area of the nature reserve fund.